OPTIMIZATION OF SUSTAINABLE PADDY AGRIBUSINESS DEVELOPMENT IN SANGGAU REGENCY, WEST KALIMANTAN PROVINCE - Roza Dewi Tambunan; Nurliza Nurliza; Eva Dolorosa (Universitas Sebelas Maret, 2022)
This study aimed to formulate a strategy for developing paddy agribusiness in Sanggau Regency West Kalimantan using a SWOT analysis of 8 respondents who were considered experts. The results of the analysis show that the strengths in formulating a strategy are the existence of a Regional Regulation (Perda); The disadvantages are the low ability, skills, and knowledge of farmers; The opportunity is that the government facilitates farmers or farmer groups who want to sell their crops; the threat is the climate. An alternative strategy that can be taken is to increase the rice planting area and production, develop markets in the border region and the outside regency, and create synergies between farmers, entrepreneurs, and the government